The nature of giving compensation and restitutions for just rape victims - R. Arif Muljohadi; Made Warka; Otto Yudianto (Technium Social Sciences Journal, 2021)
The essence of providing compensation and restitution for rape victims is to achieve justice by providing legal protection for rape victims and respecting the human rights of rape victims as the party most harmed. The concept of providing fair compensation and restitution for rape victims uses the concept of subrogation in civil law as an effective solution in solving the problem of recovering rape victims. In the subrogation concept approach, the state is a third party who takes over the responsibility for paying compensation to rape victims because the perpetrators are classified as financially incapable. In this subrogation concept, the government requires bailout funds to realize a compensation program for the recovery of rape victims, but in fact the real ones who provide compensation are the perpetrators of the crime of rape with the application of the next concept that while serving a sentence in a correctional facility, inmates are empowered as befits workers who work in prisons in a correctional facility and produce an item (product). The results of the prisoners’ work wages are partly set aside to be paid to the state treasury as a consequence of the state as a sub-roger who replaces the position of rape victims who have the right to claim the perpetrators of the crime of rape.